Spectralradiometry and caribou range classification - Meredith, Thomas C. (Rangifer, 1986)
The utility of Landsat in caribou range studies has been limited by problems of heterogeneity in cover type at the scale of pixies and by logistic barriers to ground truthing. Spectralradiometry provides an economical way of collecting ground truth data that are precisely comparable with Landsat data and which could provide a basis for hierarchic key classification rather than classification based on prinicipal components analysis. Spectral curves are presented for six common cover types and it is shown how the information could be used to develop classification criteria. Airborne data which could have provided a direct comparison with Landsat data proved to be too highly variable because of equipment constraints but there do not appear to be any significant barriers to developing the technique.